Neuro‐ and social‐cognitive clustering highlights distinct profiles in adults with anorexia nervosa. Issue 1 (3rd November 2014) - Renwick, Beth; Musiat, Peter; Lose, Anna; DeJong, Hannah; Broadbent, Hannah; Kenyon, Martha; Loomes, Rachel; Watson, Charlotte; Ghelani, Shreena; Serpell, Lucy; Richards, Lorna; Johnson‐Sabine, Eric; et al.
ABSTRACT Objective This study aimed to explore the neuro‐ and social‐cognitive profile of a consecutive series of adult outpatients with anorexia nervosa (AN) when compared with widely available age and gender matched historical control data. The relationship between performance profiles, clinical characteristics, service utilization, and treatment adherence was also investigated. Method Consecutively recruited outpatients with a broad diagnosis of AN (restricting subtype AN‐R: n = 44, binge‐purge subtype AN‐BP: n = 33 or Eating Disorder Not Otherwise Specified‐AN subtype EDNOS‐AN: n = 23) completed a comprehensive set of neurocognitive (set‐shifting, central coherence) and social‐cognitive measures (Emotional Theory of Mind). Data were subjected to hierarchical cluster analysis and a discriminant function analysis. Results Three separate, meaningful clusters emerged. Cluster 1 (n = 45) showed overall average to high average neuro‐ and social‐ cognitive performance, Cluster 2 (n = 38) showed mixed performance characterized by distinct strengths and weaknesses, and Cluster 3 (n = 17) showed poor overall performance (Autism Spectrum disorder (ASD) like cluster). The three clusters did not differ in terms of eating disorder symptoms, comorbid features or service utilization and treatment adherence. A discriminant function analysis confirmed that the clusters were best characterized by performance in perseveration and set‐shifting measures. Discussion The findings suggest that considerable neuro‐ and social‐cognitive heterogeneity exists in patients with AN, with a subset showing ASD‐like features. The value of this method of profiling in predicting longer term patient outcomes and in guiding development of etiologically targeted treatments remains to be seen. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:26–34)